Immunoproteasome subunit LMP2 expression is deregulated in Sjögren's syndrome but not in other autoimmune disorders. Issue 8 (13th January 2006) - Krause, S; Kuckelkorn, U; Dörner, T; Burmester, G-R; Feist, E; Kloetzel, P-M
Abstract : Background: The proteasome system has a pivotal role in the control of the immune response, which suggests that it might be involved in the pathogenesis of autoimmune disorders. Objective: To investigate the expression profile of selected proteasomal genes in human peripheral blood mononuclear cells in patients with a variety of autoimmune diseases compared with healthy subjects. Methods: Real time quantitative RT-PCR was used to analyse the mRNA expression pattern of the proteasome activator subunits PA28α and PA28β and of constitutive proteasome and interferon-γ-inducible immunoproteasome subunits in peripheral blood mononuclear cells. Simultaneously, protein expression of selected proteasome subunits was quantified by immunoblotting. Results: Under systemic inflammatory conditions the proteasome subunits LMP2 (β1i), LMP7 (β5i), MECL1 (β2i), and PA28α were expressed abundantly at the protein level in the vast majority of systemic autoimmune disorders. However, simultaneous mRNA and protein quantification showed a characteristic proteasome expression signature in primary Sjögren's syndrome. At the transcript level, the interferon-γ-responsive subunits LMP2 (β1i), MECL1 (β2i), and the proteasome activator subunit PA28α were markedly up regulated. In contrast, LMP2 (β1i) deficiency was evident at the protein level, indicating deregulation of proteasome expression in Sjögren's syndrome. Conclusions: These data provide evidence for a regulatory defect in the proteasome system in human autoimmune disorders, pointing to a unique role for LMP2 (β1i) in the pathogenesis of primary Sjögren's syndrome.